MEMPROGRAMKAN PENGENALAN MANAJEMEN ZAKAT INFAQ SHODAQOH DI DESA GUNUNGSARI, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Ermi Suryani; Mohamad Kharis Mubarok; Sulian Nur Andini (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
This community service aims to increase the knowledge and abilities of the people of Gunung Sari Village in managing and managing zakat, infaq and shodaqoh. The subject of this community service is the people of Gunung Sari Village, Pamijahan District, Bogor Regency, West Java Province. In this community service, activities are carried out based on transparency and participation methods. The result of this community service is that the community is able to manage zakat in a professional and organized manner, and is able to promote community welfare, especially the people of Gunung Sari Village. With this community service, it can be concluded that Gunung Sari Village is a village where zakat management is still carried out traditionally. Therefore it is necessary to manage zakat by applying the management functions of zakat, infaq and shodaqoh